2013
DOI: 10.1039/c2dt32050a
|View full text |Cite
|
Sign up to set email alerts
|

Quick photo-Fenton degradation of phenolic compounds by Cu/Al2O3–MCM-41 under visible light irradiation: small particle size, stabilization of copper, easy reducibility of Cu and visible light active material

Abstract: The present study reports the photo-Fenton degradation of phenolic compounds (phenol, 2-chloro-4-nitrophenol and 4-chloro-2-nitrophenol) in aqueous solution using mesoporous Cu/Al(2)O(3)-MCM-41 nanocomposite as a heterogeneous photo-Fenton-like catalyst. The in situ incorporation of mesoporous Al(2)O(3) (MA) into the framework of MCM-41 (sol-gel method) forms Al(2)O(3)-MCM-41 and wetness impregnation of Cu(II) on Al(2)O(3)-MCM-41 generates mesoporous Cu/Al(2)O(3)-MCM-41 composite. The effects of pH and H(2)O(2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(36 citation statements)
references
References 48 publications
1
35
0
Order By: Relevance
“…All of the samples exhibited strong absorption peaks at ca. 220 nm and 255 nm, which corresponded to the charge transfer transitions of isolated Cu(II) in coordination with lattice oxygen [31,32]. This result suggested the formation of SiAOACu in the framework of the samples [30,33,34].…”
Section: Characterization Of Catalystsmentioning
confidence: 54%
“…All of the samples exhibited strong absorption peaks at ca. 220 nm and 255 nm, which corresponded to the charge transfer transitions of isolated Cu(II) in coordination with lattice oxygen [31,32]. This result suggested the formation of SiAOACu in the framework of the samples [30,33,34].…”
Section: Characterization Of Catalystsmentioning
confidence: 54%
“…27 It is worth commenting that some studies have reported the use of copper supported catalysts for the (photo)Fenton-like reaction. 9,[28][29][30][31] Specifically it would be of interest to establish a comparison of the catalytic activity of Cu NPs with regard to that of Au and Ag under identical conditions. In the present manuscript we report such a study showing that although somewhat less active than Ag and Au, Cu/D exhibits a good balance between catalytic activity and economic competitiveness, being also after appropriate regeneration…”
Section: Introductionmentioning
confidence: 99%
“…To address these issues, different methodologies such as advance oxidation process (AOPs), adsorption, photocatalytic degradation, reverse osmosis, biological treatment, precipitation, and electrodialysis have been utilized for the elimination of both organic and inorganic pollutants from wastewater . AOPs are found to be a more successful and alternative way of removing the toxic compounds from wastewater through highly active hydroxyl radicals (OH • ) . Hydroxyl radical is found to be highly active species as the oxidation potential of OH • is E =2.73 V is more than potentials of H 2 O 2 (E =1.78 V) and Ozone (E =2.08 V) ,.…”
Section: Introductionmentioning
confidence: 56%
“…AOPs are found to be a more successful and alternative way of removing the toxic compounds from wastewater through highly active hydroxyl radicals (OH • ) . Hydroxyl radical is found to be highly active species as the oxidation potential of OH • is E =2.73 V is more than potentials of H 2 O 2 (E =1.78 V) and Ozone (E =2.08 V) ,. In photo‐Fenton reaction, H 2 O 2 along with Fe 2+ ions in presence of light are responsible for the production of reactive species like hydroxyl radicals which have the ability to oxidize the contaminants.…”
Section: Introductionmentioning
confidence: 99%